Assessing the Impact of Indiana Public Law 194 on Curbing the Concurrent Opioid Prescribing for Indiana Medicaid Enrollees - Carolina Vivas-Valencia; Nicole Adams; Paul Griffin; Nan Kong (SAGE Publishing, 2023)
Background: Several US states have introduced legislation to support the legitimate medical use of opioids while limiting misuse and diversion. One concern which has been addressed through legislation is preventing individuals from seeking opioid prescriptions concurrently from multiple providers. However, the impact of this legislation on the incidence of patients receiving concurrent prescriptions remains relatively unexplored. This study examines this phenomenon based on claims data from Medicaid enrollees and the enactment of legislation in Indiana. Methods: Indiana Medicaid claims data over the period of January 2014 to December 2019 were used to determine the changes in the percentage of individuals receiving opioid prescriptions from multiple providers within a 30-day period, that is, concurrent opioid prescription (COP) individuals. Indiana Medicaid enrollees with a diagnosis of opioid use disorder (OUD) receiving opioid prescriptions, that is, the OUD-group, were identified and separated from the enrollees without a diagnosis but receiving opioid prescriptions, that is, the non-OUD group. The mean percentages of COP individuals (with or without an OUD diagnosis) within the subset of individuals that received opioid prescriptions were compared before and after the passage of Indiana Public Law 194. Results: There were 5336 who met the criteria of COP individuals, and 2050 of those were in the OUD-group. In either group, there was a significant difference in the change in percentages (slope) before and after Indiana Public Law 194 passed. In addition, there was a significant decrease in the mean percentage of COP individuals in the non-OUD group, while the difference was not significant in the OUD group. Conclusion: Our study suggests that Indiana Public Law 194 had a positive impact on curbing COP. This study is limited by the level of details available from claims data and suggests additional studies to evaluate prescription use and prescribing practices are warranted.